Intermediate filament IFFO1 negatively regulates the migration of lung cancer cells by inhibiting the IQGAP3-Cdc42 interaction - Yuanling Ye; Fan Shen; Maoli Yan; Conghui Zhan; Jiahua Lv; Mengqin Zou; Zhifeng Wang; Shaokai Ning; Yanfei Gao; Jingxian Wu; Wen Li (Cell Death and Disease)
Abstract The metastasis of lung cancer represents a significant factor contributing to the failure of clinical treatment, and the mechanisms involved are intricate and not yet completely elucidated. Intermediate filaments, which constitute a key element of the cytoskeleton, function not only as diagnostic markers but also play a role in malignant processes, including tumor proliferation, apoptosis, and migration. The intermediate filament IFFO1 is essential for genomic stability, and its expression level serves as a prognostic indicator in various tumors. However, the functional contributions of IFFO1 in tumor progression remain inadequately understood. Our study revealed that IFFO1 is downregulated in lung cancer patients and is correlated with a poorer prognosis. The depletion of IFFO1 led to enhanced tumor proliferation both in vitro and in vivo, as well as increased cellular migration, alterations in the cytoskeleton and modifications in GTPase-mediated signal transduction. Mechanically, IFFO1 was found to interact directly with the GTPase-related scaffold IQGAP3 through the 2 A coiled-coil domain, which was critical for the inhibition of cellular mobility. Moreover, the increased cell migration observed in IFFO1-deficient cells was substantiated as being facilitated by IQGAP3. Finally, IFFO1 was shown to inhibit the association of IQGAP3 with its effector Cdc42 in a dose-dependent manner. Our study demonstrates the multifaceted roles of IFFO1 in lung cancer by modulating the IQGAP3-Cdc42 axis and suggests the potential for identifying tumor targets through the examination of intermediate filament networks and their associated co-factors.